Financial Performance Assessed From Economic Value Edded (EVA) and Market Value Added (MVA) Cases in the Cosmetics Sub-Sektor and Household Needs Listed On the BEI - Heny Triastuti Kurnianingsih; Sri Rahayu (Budapest International Research and Critics University, 2020)
Assessment of financial performance is an activity that is very important for companies, especially investors as a material consideration in making investment decisions. The methods used to measure financial performance include the ecomonic value added and market value added The purpose of this study is to determine of financial performance using EVA and MVA method in the cosmetics sub-sector and household need listed on the BEI and what factors cause negative eva and mva value in the company. The analysis technique used is quantitative descriptive analysis with samples of 3 companies. The results of the study indicate that PT. Akasha Wira Internasional Tbk has a negative EVA value for 2013-2015 year and positive value for 2016-2017 year. Whereas, MVA is positive value for 2013-2016 year and negative value in 2017 year. PT. Martina Berto Tbk has EVA and MVA which are negative value during the study period, namely 2013-2017 year. PT. Unilever Indonesia Tbk has EVA and MVA which are positive value during the study period, namely 2013-2017 year. EVA is negative value because the rate of return on net operating profit after tax (nopat) is less than capital charges. Whereas, MVA is negative value because value of the company is less than invested capital.